Harnessing the microbiome to improve clinical outcomes for cancer, transplant, and immunocompromised patients in the intensive care unit (ICU) - Nieves, Lizbeth; Roach, Alexandra; Hunter, Joseph; Smeh, Sarah; Islas, Andrew; Islas, Ariana; Blattman, Joseph; Di Palma, Michelle (Frontiers in Cellular and Infection Microbiology, 2025)
In recent decades, there has been a growing emphasis on understanding how the architecture of the human microbiome can impact typical biological processes and patient clinical outcomes. In fact, microbiome modifications and modulations have not only been associated with impacts on general health and well-being but have also been shown to yield differences in patient responsiveness to vaccines, medications, and chemotherapeutic regimens. Much of this influence likely stems from how changes in the microbiome result in differences in microbial communities and the subsequent release of microbial-derived metabolites that can alter typical immunological processes. Understanding how microbial composition can impact patient responsiveness can be particularly important in the intensive care unit (ICU), where the efficacy of medications and treatments can result in negative patient outcomes if unsuccessful. Clinical scientists have further developed the concept of the pathobiome, a disease-promoting microbiome whose development can be associated with dysbiosis. Understanding how the microbiome and its associated components can impact patient responsiveness, especially in the ICU, must be further researched and understood. Here, we analyze what causes variances in the microbiome and pathobiome in significant immunocompromised populations, including cancer patients and transplant recipients, and how variances in the microbiome can impact patient outcomes in the ICU. Further, we detail potential future applications of how our understanding of what impacts the human microbiome during the treatment of these populations may be exploited to improve patient prognosis.